Orientation and Mobility Career, College, and Community Readiness Standards: A Delphi Study. (May 2019) - Tellefson, Mary J.; Koehler, William S.; Botsford, Kathryn D.; Cook, Leanne
Introduction: Performance standards drive current instructional practice. Disability-specific curricula is a critical component in preparing children for postsecondary transition. Currently, no standards govern instruction in orientation and mobility (O&M) skills for children with visual impairments. Standards for O&M would provide structure for educational equity in assuring that students with visual impairments receive a free and appropriate education. Method: This study used Delphi survey methods to determine consensus on the validity of the Orientation and Mobility Career, College, and Community Readiness Standards (O&M CCCRS). Consensus was measured as 80% or better agreement. Three survey rounds were initiated and two were completed by a purposive sample of certified orientation and mobility specialist (COMS) from two participant groups: Seven COMS from primary and secondary school–based settings and three from personnel preparation. Results: This Delphi study achieved consensus on the O&M CCCRS five student-performance standards (end of Grade 12 or age 21 years) as well as the corresponding age- and grade–level performance indicators at ages 24 months, 4 years, end of Grade 3, end of Grade 7, and end of Grade 12. Consensus was reached on all but two performance indicators (83 of the 85). Discussion: The Round 1 survey established validity of five O&M Domains: (1) Concept Development, (2) Sensory Development, (3) Orientation and Mapping, (4) Travel Techniques, and (5) Communication, Personal Safety, and Advocacy. Subsequent survey rounds found that 80% of participants agreed on the inclusion of 83 of the 85 performance indicators corresponding to those domains. Implications for practitioners: Alignment of O&M standards to Common Core Standards empowers teams to justify the instructional time, to document skill acquisition relative to the benchmarks of general-education peers, and to show where O&M skills support progress in common core and state learning standards.